PENGARUH LIMBAH PLASTIK LDPE TERHADAP CAMPURAN ASPHALT CONCRETE– BASE COURSE (AC–BC) DENGAN METODE MARSHALL ( 21-28 ) - Ika Sulianti; M. Sazili Harnawansyah; Merry Andika Putri; Abdul Haris Chudori (PILAR, 2019)
The purpose of this study is to find out whether the addition of plastic waste Low Density Polytlene (LDPE) as a alternative subsitution of Marshall characteristic on AC-BC mixture. First study done by made sample, the optimum asphalt contentused is  5,75%, and then made sample use plastic waste contenct was 10%, 11%, 12%, 13%, and 14%. The best result of Marshall Test was obtained at 14%, while VIM and VFA out of range of spesification.